Can fiscal incentives stimulate regional investment in the Philippines? An update of empirical results - Renato E. Reside (University of the Philippines, School of Economics (UPSE), 2007)
This study updates earlier estimates of the sensitivity of regional investment flows in the Philippines to fiscal incentives - income tax holidays and other fiscal inducements provided by government. All other factors held constant, the strength and significance of the investment-inducing effect of a given set of incentives can be gleaned from the size and significance of proxies used for incentives in investment regression equations. Using regional data, the regressions confirm that proxy variables for incentives are not good predictors for regional investment in the Philippines. The results reinforce previous empirical findings that, consistent with international evidence on the power of incentives, the power of incentives to influence patterns of regional investment within the Philippines is also weak. This reinforces the policy implications of Reside's (2006) paper - rather than waste resources providing ineffective investment subsidies, each region in the country would be better off if the Philippine government streamlined fiscal incentives, raised a sufficient amount of taxes and then procured the productivity-enhancing public goods (access to good .education and infrastructure) that really mattered more for investment and investors.
Keywords: 330; Investitionsklima; Subvention; Regionale Inzidenz; Schätzung; Philippinen